1994
DOI: 10.1111/j.1550-7408.1994.tb06085.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Amongst Leishmania by Polymerase Chain Reaction and Hybridization with Small Subunit Ribosomal DNA Derived Oligonucleotides

Abstract: A method for discriminating among Leishmania is described, based upon small subunit ribosomal DNA sequence differences. The method was to amplify the entire 2.2 kb small subunit rDNA by polymerase chain reaction using conserved primers specific for the 5' and 3' termini of the small subunit ribosomal RNA, and then hybridize the product dotted onto nylon membranes with labeled oligonucleotides. The design of the hybridization probes was based upon complete small subunit rDNA sequences from L. amazonensis, L. ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
24

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 26 publications
(24 reference statements)
0
72
0
24
Order By: Relevance
“…Reactions were performed in a final volume of 50 µl containing 1X PCR buffer, 2 mM MgCl 2 , 0.2 mM dNTPs, 0.2 µM of each primer and 2 U Taq DNA polymerase. The first PCR was performed with primers S4 (5'-GAT CCA GCT GCA GGT TCA CC -3') and S12 (5'-GGT TGA TTC CGT CAA CGG AC -3') as described by Uliana et al (1994). The DNA was denatured at 94ºC for 3 min and then cycled 35 times at 94ºC for 1 min, at 50ºC for 1 min, and at 72ºC for 1 min.…”
mentioning
confidence: 99%
“…Reactions were performed in a final volume of 50 µl containing 1X PCR buffer, 2 mM MgCl 2 , 0.2 mM dNTPs, 0.2 µM of each primer and 2 U Taq DNA polymerase. The first PCR was performed with primers S4 (5'-GAT CCA GCT GCA GGT TCA CC -3') and S12 (5'-GGT TGA TTC CGT CAA CGG AC -3') as described by Uliana et al (1994). The DNA was denatured at 94ºC for 3 min and then cycled 35 times at 94ºC for 1 min, at 50ºC for 1 min, and at 72ºC for 1 min.…”
mentioning
confidence: 99%
“…Another advantage of this technique is that it requires low parasite density, i.e. a minimum level of 10³ parasites/mL 20 . This same author has reported that given the high sensitivity of the test, it is possible to perform PCR with just 10 parasites and to detect the band in the electrophoresis gel.…”
Section: Discussionmentioning
confidence: 99%
“…testing for Leishmania in the aspirate of bone marrow, lymph nodes, blood or skin, is an invasive method 5 that calls for specialist knowledge and thus is not practicable when there is a high demand for these exams. To resolve this dilemma, the PCR technique offers a solution by means of specific primers that make identification of the various Leishmania species possible 19,20,22 . Another advantage of this technique is that it requires low parasite density, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…After DNA extraction, two PCR methodologies were used. The first (the initial screening) identified trypanosomatids by means of primers that amplify ribosomal DNA genes (rDNA) 20 . The second methodology, which used primers that were complementary to the miniexon sequences, enabled the Leishmania 16 species among the trypanosomatids to be identified.…”
Section: Methodsmentioning
confidence: 99%